Population of brown shrike (Lanius cristatus) in grassland of University Putra Malaysia - Ahmed Eshkab, Ibrahim (1999)
The purpose of the study is to determine Brown Shrike (Lanius cristatus) population size at grassland area of University Putra Malaysia. Transect survey method was employed for the data collection. Altogether five lines were established in the study area. Each line was surveyed for three days - two surveys for each day (in the morning and afternoon). Distance Version 2.2 software which was originally developed to allow comprehensive analysis of distance sampling data was used for the estimation of Brown Shrike density. The results of the observation during the days of sampling, shows that the density estimates of Brown Shrike is in the range of 0.35 - 0.81 birds per hectare. The population size in the 258.06 hectares UPM grassland is ranging from 131.6 - 209.3 birds. The population of Brown Shrike in the study area was considerably high compared to other areas in different part of Asia.